NATURE OF THE LATE CARBONIFEROUS TO TRIASSIC MAGMATISM ALONG THE NORTHERN MARGIN OF THE NORTH CHINA BLOCK: LINK WITH THE EVOLUTION OF THE CENTRAL ASIAN OROGEN - Peng Peng; Mingguo Zhai; Xiangdong Su; Taiping Zhao; Yanyan Zhou (Геодинамика и тектонофизика)
There are two episodes of magmatism along the northern margin of the North China block during the Late Carboniferous to Late Triassic, one at 310–250 Ma (Late Carboniferous to Permian) and the other at 235–210 Ma (Late Triassic). The former group comprises plutonic rocks (gabbro-diorite-monzodioritemonzogranite-granite), mafic to intermediate dykes (diorite to dolerite) and a few felsic volcanics (andesite to dacite).